Plant Glycosyltransferases Beyond CAZy: A Perspective on DUF Families - Hansen, Sara F.; Harholt, Jesper; Oikawa, Ai; Scheller, Henrik V. (Frontiers in Plant Science, 2012)
The Carbohydrate Active Enzyme (CAZy) database is an invaluable resource for glycobiology and currently contains 45 glycosyltransferase families that are represented in plants. Glycosyltransferases have many functions in plants, but the majority are likely to be involved in biosynthesis of polysaccharides and glycoproteins in the plant cell wall. Bioinformatic approaches and structural modeling suggest that a number of protein families in plants include glycosyltransferases that have not yet been identified as such and are therefore not included in CAZy. These families include proteins with domain of unknown function (DUF) DUF23, DUF246 and DUF266. The evidence for these proteins being glycosyltransferases and their possible roles in cell wall biosynthesis is discussed.